Autoimmune Enteropathy in an Ulcerative Colitis Patient. Issue 1 (2018) - Rodriguez, Nicolette J.; Gupta, Neil; Gibson, Joanna
ABSTRACT : N/A: Autoimmune enteropathy is a rare but severe disorder with significant immune‐mediated changes. We present a 54‐year‐old woman with history of refractory ulcerative colitis status post total colectomy with end ileostomy who presented 1 month after her surgery with high ostomy output of 4 L/d. After a negative workup, ileoscopy with biopsies showed severe chronic active ileitis. Enteroscopy revealed diffuse chronic enteritis concerning for autoimmune enteropathy. She was started on budesonide and intravenous solumedrol, but her ostomy output remained high. She was then started on cyclosporine and later tacrolimus with significant clinical improvement and normalization of ostomy output on tacrolimus.